Self-imposed liquidity constraints via voluntary debt repayment - Vihriälä, Erkki (Journal of Financial Economics, 2023)
Debt-repayment flexibility should help temporarily liquidity-constrained households but not necessarily households struggling to save. In a natural experiment in which households can apply for free mortgage-repayment flexibility, I find that two-thirds of liquidity-constrained applicants with high-cost debt voluntarily restrict flexibility and forgo, on average, 4,070 EUR of low-cost liquidity. An overconsumption tendency reflecting self-control problems can explain the voluntary liquidity restrictions as well as the persistent liquidity constraints, the consumption drop at the predictable end of flexibility, and saving in other illiquid assets. Self-imposed liquidity constraints reflect characteristics instead of circumstances and reduce the potency of debt-forbearance offers in recessions.